A Novel Biomimetic Nanoprobe as a Photoacoustic Contrast Agent - Huang, Xin; Shen, Ao; Peng, Rui; Chen, Sheng; Lin, Shitao; Ding, Shangwei; Li, Huan; Zhou, Dazhi (Frontiers in Chemistry, 2021)
Specific detection of tumors is of pivotal importance to cancer prevention and therapy, yet a big challenge. Photoacoustic imaging (PAI) as an emerging non-invasive modality has shown great potential in biomedical and clinical applications. The performance of PAI largely depends on the light-absorption coefficient of the imaged tissue and the PAI contrast agent being used, either endogenously or exogenously. The exogenous contrast agents developed so far have greatly helped improving PAI, but still with some limitations, such as lack of targeting capacity and easy clearance by the host immune system. Herein, we fabricated a biomimetic nanoprobe with cell membrane coating as a novel PAI contrast agent, namely MPD (Membrane-coated Poly(lactic-co-glycolic acid) (PLGA)/Dye). In brief, the organic dye 1,1’-dioctadecyl-3,3,3’,3’-tetramethylindotricarbocyanine iodide (DiR) was encapsulated by Food and Drug Administration approved polymer, Poly(lactic-co-glycolic acid) (PLGA) and form polymer nanoparticles by emulsification. The nanoparticles are further coated with cancer cell membrane to form MPD. MPD have outstanding biocompatibility, tumor specificity and in vivo stability. Thus, MPD is a versatile NIR-I theranostic nanoplatform for PAI-guided cancer diagnosis and therapy.